2018–2019 Vegetable Production Handbook Chapter 3: Principles and Practices of Irrigation Management for Vegetables - Lincoln Zotarelli; Michael D. Dukes; Guodong Liu; Eric H. Simonne; Shinsuke Agehara (EDIS)
This 8-page fact sheet is chapter 3 of the 2018–2019 Vegetable Production Handbook. It is a minor revision written by Lincoln Zotarelli, Michael D. Dukes, Guodong Liu, Eric H. Simonne, and Shinsuke Agehara, and published by the Horticultural Sciences Department, December 2018.